INVESTIGATION OF INTERFERENCE INFLUENCE OF BLADE ROWS ON LOSSES IN AXIAL COMPRESSOR STAGE - Tereshchenko, Yuriy M.; Doroshenko, Ekaterina; Tereshchenko, Yuriy Yu.; Gumenyuk, Pavel (Proceedings of National Aviation University, 2018)
Purpose: the purpose of this work is to investigate the total pressure losses in the input guide vanes, in the rotor wheel and the guide vanes of the axial compressor stage taking into account their gas-dynamic interference. Methods: the study was carried out by numerical simulation of three-dimensional flow in the stage of an axial compressor. An unstructured adaptive computational grid is constructed. The gas dynamic calculation of the flow in the stage of the axial compressor is performed using the Navier-Stokes system of equations, which was closed by the SST turbulent model. Results: a series of gas-dynamic flow calculations was performed at different values of the axial velocity at the inlet to the compressor stage. The circuit velocity at the peripheral radius in the calculated mode was u= 238.64 m/s. The coefficient of velocity at the entrance to the stage varied in the range =0.35…0.7. Based on the calculation results, the dependences of the total pressure loss coefficients from the input velocity coefficient for various elements of the stage of the axial compressor were constructed. Analysis of the results of the study shows that the greatest contribution to the overall balance of total pressure losses is made by losses in the guide vanes. Discussion: losses in the guide vanes increase due to the gas-dynamic interference of the rotor wheel and the guide vanes. The mutual influence of the blade rows of the rotor wheel and the guide vanes leads to a significant transformation of the velocities and pressures in the interblade channels. As a consequence, there is a redistribution of losses caused by circumferential and radial flow irregularity, end-flow and centrifugal forces. It can be expected that a reduction in the level of losses in the step of the axial compressor can be achieved by influencing the boundary layer in the end clearance of the rotor wheel.